The Architectonic Experience of Body and Space in Augmented Interiors - Pasqualini, Isabella; Blefari, Maria Laura; Tadi, Tej; Serino, Andrea; Blanke, Olaf (Frontiers in Psychology, 2018)
The environment shapes our experience of space in constant interaction with the body. Architectonic interiors amplify the perception of space through the bodily senses; an effect also known as embodiment. The interaction of the bodily senses with the space surrounding the body can be tested experimentally through the manipulation of multisensory stimulation and measured via a range of behaviors related to bodily self-consciousness. Many studies have used Virtual Reality to show that visuotactile conflicts mediated via a virtual body or avatar can disrupt the unified subjective experience of the body and self. In the full-body illusion paradigm, participants feel as if the avatar was their body (ownership, self-identification) and they shift their center of awareness toward the position of the avatar (self-location). However, the influence of non-bodily spatial cues around the body on embodiment remains unclear, and data about the impact of architectonic space on human perception and self-conscious states are sparse. We placed participants into a Virtual Reality arena, where large and narrow virtual interiors were displayed with and without an avatar. We then applied synchronous or asynchronous visuotactile strokes to the back of the participants and avatar, or, to the front wall of the void interiors. During conditions of illusory self-identification with the avatar, participants reported sensations of containment, drift, and touch with the architectonic environment. The absence of the avatar suppressed such feelings, yet, in the large space, we found an effect of continuity between the physical and the virtual interior depending on the full-body illusion. We discuss subjective feelings evoked by architecture and compare the full-body illusion in augmented interiors to architectonic embodiment. A relevant outcome of this study is the potential to dissociate the egocentric, first-person view from the physical point of view through augmented architectonic space.